Strain-induced conductive network and memory effect of maximum strain in liquid metal hierarchical structure - Wang, S.; Li, F.; Li, S.; Cao, J.; Li, S.; He, Z.; Li, R. W.
Liquid metals based on gallium have attracted considerable attention for flexible electronics, thanks to their excellent combination of stretchability and conductivity. Nevertheless, the degradations of electrical properties under deformation and effective tune of electrical resistance like a rheostat remain problems to be solved. Herein, a hierarchical structure of liquid metal particles is prepared by the combination of oxidation process and two-step physical vapor deposition. Owing to the rupture of particles, the electromechanical response allows resistance to irreversibly decrease in response to increased tensile strains and remain constant during strain release. Furthermore, the rupture level of core-shell structural particle can be controlled by the applied strain, resulting in strain-induced electrical properties. Notable characteristics include memory effect of maximum strain. As long as the strain is smaller than the maximum strain experienced previously, the strain-induced conductive network maintains nearly constant resistances to cyclic deformations (R/R0 < 1 percent above 1000 cycles). Finally, only based on the resistance before and after deformation, a class of devices is developed specifically for measuring and memorizing the maximum strain. The batteryless operation feature allows the device promising applications in long-term monitoring.
Keywords: STRAIN-HISTORY BEHAVIOR; HIERARCHICAL STRUCTURE; MEMORY EFFECT OF MAXIMUM STRAIN; BATTERY-FREE